Syysseminaarin satoa - Holopainen, Tiina; Salmi, Leena; Taivalkoski-Shilov, Kristiina; Tuominen, Tiina (Suomen kääntäjien ja tulkkien liitto – Finlands översättar- och tolkförbund ry, 2025)
This article reports on the autumn seminar of the Teachers’ and Researchers’ Section of the Finnish Association of Translators and Interpreters, held at the University of Turku in August 2024. The theme of the seminar was cooperation in teaching, addressed in two presentations as well as in learning café discussions together with the participants. In this article, we summarize the presentations and the learning café discussions.